DNA methylation programming and reprogramming in primate embryonic stem cells - Cohen, Netta Mendelson; Dighe, Vikas; Landan, Gilad; Reynisdóttir, Sigrún; Palsson, Arnar; Mitalipov, Shoukhrat; Tanay, Amos (Genome Research, 2009)
DNA methylation is an important epigenetic mechanism, affecting normal development and playing a key role in reprogramming epigenomes during stem cell derivation. Here we report on DNA methylation patterns in native monkey embryonic stem cells (ESCs), fibroblasts, and ESCs generated through somatic cell nuclear transfer (SCNT), identifying and comparing epigenome programming and reprogramming. We characterize hundreds of regions that are hyper- or hypomethylated in fibroblasts compared to native ESCs and show that these are conserved in human cells and tissues. Remarkably, the vast majority of these regions are reprogrammed in SCNT ESCs, leading to almost perfect correlation between the epigenomic profiles of the native and reprogrammed lines. At least 58% of these changes are correlated in cis to transcription changes, Polycomb Repressive Complex-2 occupancy, or binding by the CTCF insulator. We also show that while epigenomic reprogramming is extensive and globally accurate, the efficiency of adding and stripping DNA methylation during reprogramming is regionally variable. In several cases, this variability results in regions that remain methylated in a fibroblast-like pattern even after reprogramming.